Granville Sharp's canon and its kin semantics and significance - Wallace, Daniel B. (Lang, 2009)
Granville Sharp's Canon and Its Kin explains that the semantics of the article-substantive-KAI-substantive construction (TSKS) have been largely misunderstood and that this misunderstanding has adversely impacted the exegesis of several theologically significant texts. --from publisher description
Keywords: Jesus Christus; Jesus Christ -- Divinity; Sharp, Granville <1735-1813>; Sharp, Granville -- 1735-1813; Bibel -- Neues Testament; Greek language, Biblical -- Article; Griechisch; Substantiv; Semantik